Detection of Campylobacter pylori in stomach tissue by DNA in situ hybridisation. - Van den Berg, F M (1989)
A non-radioactive DNA in situ hybridisation (DISH) protocol was developed. It requires the use of biotinylated Campylobacter pylori DNA as the probe to detect C pylori DNA in routinely embedded stomach biopsy specimens. In sequential tissue samples from a 58 year old woman with recurrent chronic active gastritis the C pylori probe hybridised with bacteria whenever they were histologically visible. When no bacteria were visible histologically, hybridisation was negative with one exception. In a single biopsy specimen without visible C pylori, hybridisation occurred with the surface of the antrum epithelium, while control hybridisation with a heterologous probe remained negative. From a parallel biopsy specimen taken at the same time the C pylori culture was positive. It is concluded that DISH, although more laborious than routine staining techniques, may be more sensitive in that it detects bacteria very easily, even when sections are not counterstained or when they are present in low numbers, and that bacteria which do hybridise are unequivocally identified as C pylori and not Campylobacter-like organisms.